UPAYA PELESTARIAN ADAT PERNIKAHAN ETNIS SIBOLGA-TAPANULI TENGAH MELALUI TRADISI LISAN - Anggira, Suci; Arfanti, Yulia (Universitas Islam Sumatera Utara, 2023)
Culture is an activity that is carried out by the community repeatedly and becomes the basis for behavior, not only seen as a work or idea which then becomes a cultural object such as art or tools and other objects that reflect an area. Therefore, preserving adat is important for the people. One of the efforts made is through oral tradition. The purpose of this research is to look at efforts to preserve the traditional marriage traditions of Sibolga- Central Tapanuli ethnic through oral tradition. This study applies a qualitative approach that aims to describe the description of the phenomenon of the variables studied. To describe the variables of this study, the data used consisted of primary data through interviews with informants and secondary data obtained from books or records that explained the implementation of the traditional Sibolga-Central Tapanuli ethnic marriage. The instruments used to collect data consisted of interviews and observation sheets. After the data is collected, the data is then analyzed through a process of data reduction and data interpretation. Based on the results of observations made during the research, some information was obtained that oral traditions were still effectively carried out in an effort to preserve the customs and culture of an ethnic group. Techniques that can be taken in efforts to inherit culture are through natural inheritance which is carried out by the older generation to the younger generation through the implementation of culture which can be witnessed by the younger generation. Traditional leaders through traditional institutions will continue to make efforts so that their customs and culture are passed on to the younger generation through various means, such as publishing books on customary practices, providing studios for young people to practice their ethnic arts, and providing guidance in implementing culture.